Nasal Myiasis: A Case Report - Shokrollah SALMANZADEH; Mahmoud RAHDAR; Sharif MARAGHI; Fatemeh MANIAVI (Tehran University of Medical Sciences, 2018)
Myiasis is caused by invasion of larvae stage of dipterans fly in living tissue of vertebrate host including human and animals. The most important family is Calliphoridae and included Calliphora, Lucilia, Chrysomyia and Cochliomyia genus. A 35-yr-old man with gastric cancer history referred to Golestan Hospital in Ahvaz Southwest of Iran in 2015. He was infected by nasal myiasis from Lucilia spp. in ICU. The genus of third larvae stage was identified by microscopic examination and culture of pupa. The population of flies inducing myiasis should be controlled in hospitals.